(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Light gauge steel lipped channel sections are being used popularly in shops, factories, automobile engineering and industries on account of their high strength to width ratio, simplicity in construction, flexibility in fabrication and high structural efficiency. A lot of research work has been carried out to study the structural behavior of axially loaded light gauge steel lipped column sections considering different parameters. The present paper focuses on the experimental study of structural behavior of light gauge steel channel sections under axial compression loading .Finite element analysis of the section is also done using Abaqus software of same load. In this work we have studied the behaviour of the light gauge section under axial compression loading.different specimens of the section where considered with and without lip, v- stiffeners and rectangular stiffeners for deriving the load carrying capacity of section. The analysis and design of the I section was done using previous work while the analytical work was carried out using finite element method with ABAQUS software. Further the experimental validation was done using true length specimen and setup was prepared and tested under axial compression loading. The results of this experimental investigation indicated that the load carrying capacity of the light gauge channel section is enhanced by using different stiffener and lips.